The Effect of Absorbed Dose and Chemical Composition On the Ionic Conductivity of 1-Vinylimidazole-Grafted PVDF Membranes Made Via Y-Ray Induced Grafting - Lepit, A.; Mustaffa, M.; Jaafar, N. K.; Aini, N. A. (International Journal of Membrane Science and Technology, 2023)
The effect of ?-ray on the copolymerization of 1-Vinylimidazole (VIm) onto polyvinyl fluoride (PVDF) is dependent on the absorbed dose, various solvents, and Iron concentration (II). Using radiation-induced grafting techniques, develop an alternative proton-exchange membrane (PEM) based on PVDF as the primary polymer and VIm as the monomer. Gravimetric analysis, FTIR, and conductivity investigation were utilized to characterize the physico-chemical properties of the grafting membrane. PEM, also known as PVDF-g-P1VIm, was synthesized and functionalized by sulfuric acid doping. The proportion of dose absorbed, the degree of grafting (DG), the ion exchange capacity (IEC), and water uptake (WU) all correlate with the membrane grafting performance. The C-H bonds exhibited decreased intensity and the peak location moved considerably in FTIR, indicating PVDF-VIm grafting. DG and IEC influence the ionic conductivity of the grafting PEM. The grafted membranes proved to have humidity dependent on proton conductivity with a range of 0.136 mScm-1 (room temperature) and 3.02 mScm-1 (373 K) containing IEC levels of 0.065 and 0.107 meq./g, respectively. PVDF-g-P1VIm membranes exhibit potential in the field of PEM membranes for use in hydrogen fuel cells or water treatment.